2021
DOI: 10.1016/j.jbc.2021.100549
|View full text |Cite
|
Sign up to set email alerts
|

The scrambled story between hyaluronan and glioblastoma

Abstract: Advances in cancer biology are revealing the importance of the cancer cell microenvironment on tumorigenesis and cancer progression. Hyaluronan (HA), the main glycosaminoglycan in the extracellular matrix, has been associated with the progression of glioblastoma (GBM), the most frequent and lethal primary tumor in the central nervous system, for several decades. However, the mechanisms by which HA impacts GBM properties and processes have been difficult to elucidate. In this review, we provide a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 227 publications
4
42
0
Order By: Relevance
“…It should be noted that in the present study, tumor cell infiltration has not been quantified in the white matter specimens. Nevertheless, exploring the possible association of peritumoral white matter elasticity with prominent traits of its histology, like tumor cell infiltration, as well as myelin and hyaluronan [ 61 ] content and properties, factors that play a key role in the interaction between glioma and extracellular matrix [ 62 , 63 , 64 ], would be an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in the present study, tumor cell infiltration has not been quantified in the white matter specimens. Nevertheless, exploring the possible association of peritumoral white matter elasticity with prominent traits of its histology, like tumor cell infiltration, as well as myelin and hyaluronan [ 61 ] content and properties, factors that play a key role in the interaction between glioma and extracellular matrix [ 62 , 63 , 64 ], would be an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Out of these, HYAL1 (present in lysosomes) is mainly responsible for HA degradation into oligo–, di–, and monosaccharides while HYAL2 (localized to the cell surface via a GPI linker) degrades HA into fragments of about 20 kDa. These HYAL2 created fragments are either released into the microenvironment or internalized by HA receptors such as CD44 to be further degraded by HYAL1 [ 44 , 45 , 46 ]. Two additional proteins with hyaluronidase activity have more recently been discovered that process HA into intermediate–sized LMW fragments: the transmembrane protein TMEM2 [ 47 ] and KIAA1199 (CEMIP, HYBID) [ 48 ].…”
Section: The Hyaluronomementioning
confidence: 99%
“…It has been proposed that the aggressiveness of GBM depends on the co-expression of HAS and hyaluronidases (95). In this sense, based on the fact that 4-MU is a small molecule able to cross the blood brain barrier (96), Pibuel et al proposed its use as an interesting therapeutic strategy to complement GBM treatment (65). These authors demonstrated that, in the GL26 murine GBM cell line, 4-MU diminished HA synthesis while increasing apoptosis and decreasing cell proliferation and migration (66).…”
Section: Glioblastomamentioning
confidence: 99%